The THE EFFECT OF REALISTIC MATHEMATICS LEARNING APPROACH ON CONCEPT UNDERSTANDING - Teguh Santoso Teguh; Siti Wulan Purnawati; Eko Yulio Susanto (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2021)
Students' understanding of concepts in mathematics learning is still having difficulties. The purpose of this study was to determine the effect of a realistic mathematics approach on students' understanding of the SPLDV concept. This research is experimental research with one group pretest-posttest design. The place where this research was carried out was SMP Bahrul Maghfiroh Malang. The data collection technique used in this study was a written test. The data analysis technique used is quantitative analysis, namely using descriptive statistics and inferential statistics. The results obtained from the calculation of the hypothesis test Z count> Z table, namely (16,733> 1,645), it can be concluded that H_0 is rejected and H_a is accepted, so that there is a better effect of learning with a realistic mathematics approach in improving students' understanding of the SPLDV concept. Students look more relaxed in participating in learning.